Regulatory enforcement, gender quotas, and women on board: evolution and firm performance - Mohamed Omran (International Business Logistics Journal)
One of Sustainable Development Goals (SDGs) established by the United Nations in 2015 is goal 5 (SDG 5 or global goal 5) concerns gender equality. Target 5.5 (Ensure women's full and effective participation and equal opportunities for leadership at all levels of decision-making in political, economic, and public life) is seen as an important cornerstone of gender equality. Furthermore, indicator 5.5.2 considers the proportion of women in managerial positions as a mean towards achieving the global goal 5.   So, there are several questions that deserve answers: Does gender diversity matter? And what are its implications on regulatory environment, and its effects on firm performance? The easiest to answer of these three questions is probably the first, since there is bulk of theoretical arguments and several empirical findings show that companies that enjoy an acceptable level of board diversity, in terms of women participations on boards, tend to be more efficient and more profitable than those with less diversity. The second question is perhaps the most interesting because it has, recently, spawned rich actions taken by different policymakers and regulators to impose women quotas on boards, mainly for publicly traded companies. The upshot of these actions is to empower women economically, on the ground that women participation in economic activities and decision-making will have a positive impact on the economy at large. What makes this finding interesting is its implications for the third question, since there is no consensus in the literature and empirical evidence on the impact of women on boards on firm performance. As a result, one could conclude that gender diversity, in terms of women participation on boards, or the lack of it is immaterial to firm performance.